EFFECT OF SAPONIN AS DEFAUNATING AGENT ON IN VITRO RUMINAL FERMENTATION OF FORAGE AND CONCENTRATE - Hanim, C.; Yusiati, L.M.; Alim, S. (Diponegoro University, 2009)
nin level in fermentation medium (0, 0.1, 0.2, or 0.3 mg/ml), and many kinds of feed (king grass,rice bran, and king grass:rice bran, 60:40 w/w) on protozoa numbers, ammonia concentration, microbialprotein, pH and cellullase activity. Each treatment was consisted of three replicates. Fermentation wasdone in syringe and used in vitro gas production medium. The data obtained were analyzed by varianceanalysis using factorial design (4x3). The differences between mean values were analyzed by Duncan’snew multiple range test (DMRT). The result showed that protozoa numbers decreased 17.22, 42.73 and49.57% (P<0.01) for 0.1, 0.2, and 0.3 mg/ml saponin, respectively from 8.19×103/ml in the control. Theaddition of 0.1 mg/l saponin increased ammonia concentration from 33.04 mg/100 ml (without saponin)to 37.12 mg/100 ml (P<0,01), whereas the addition of 0.2 and 0.3 mg/ml saponin decreased ammoniaconcentrations by 1.69 and 16.50% (P<0.01) compared to the control. Microbial protein, cellullaseactivity and pH were not affected neither by saponin nor kind of feed. Protozoal numbers and ammoniaconcentration in the rumen were lower (P<0.01) with king grass as substrat than that with rice bran, orking grass: rice bran. In general, no interactions between saponin and kind of feed were observed, exceptfor ammonia concentration. It can be concluded that level of 0.2 mg/ml saponin have antimicrobialproperties, particularly in suppressing protozoa, which may prove beneficial to ruminal fermentation andmay lead to lower ruminal ammonia concentration, but it did not have negative effect on pH, microbialprotein and cellullase activity. King grass as a substrate decreases protozoa numbers and ammoniaconcentration.